Trehalose as a cryoprotectant in freeze-dried wheat sourdough production - Stefanello, Raquel Facco; et. al. (2017)
Sourdough, a mixture of wheat flour and water, fermented by the action of lactic acid bacteria (LAB) and yeasts, presents some technological advantages, such as improvement in dough structure, flavor, aroma, bread texture, and shelf life. Few studies related to methods of preservation of sourdoughs are currently available. This work aimed to test the cryoprotective effect of trehalose on microorganism survival and its effect on freezing, freezedrying and storage of freeze-dried sourdough, and to molecularly identify predominant bacteria and yeasts. Refined and whole wheat flour were used to prepare the sourdough. On the 14th day of production, varying amounts of trehalose were added (0, 10 and 15%) and the sourdough was freeze-dried. The cryoprotective effect of trehalose was evaluated before and after freezing, after freeze-drying, and after 15, 30 and 45 days of storage. Predominant microorganisms were molecularly identified through amplification and sequencing of rDNA fragments. Addition of trehalose promoted a cryoprotective effect survival of microorganisms, and it was more significant for LAB. Lactobacillus plantarum, Lactobacillus fermentum, Saccharomyces cerevisiae, Pichia anomala and Pediococcus pentosaceus, were the main species recovered.